(untitled) (The Research of Medical Science Review, 2024)
This study examines the prevalence of Cutaneous Leishmaniasis (CL) in District Upper Dir, Pakistan, with a focus on gender, occupation, and socioeconomic status. CL is primarily caused by Leishmaniamajor and Leishmania tropica, transmitted by female sandflies. The study finds significant variations in infection rates across regions in Tehsil Wari, influenced by demographic factors and living conditions. Regions like Wari and Kotkay have moderate prevalence rates (15.0% and 10.5%) with balanced gender distributions, primarily affecting students and young workers from low socioeconomic backgrounds. In contrast, Gogyal and Sahibabad show high male prevalence (22.0% and 20.0%), linked to farming activities. Female-dominated areas like Serai and Pashata have moderate prevalence, with most cases affecting stay-at-home spouses or retirees. Other regions like Dogram, Shakani, and Dislawar show mixed gender distributions, reflecting diverse occupational backgrounds. Key risk factors include recent travel (76.94%), higher prevalence in unemployed individuals, and increased exposure for agricultural workers and laborers. Housing conditions, with most respondents living in brick or cement homes, offer some protection against environmental factors. The urban-rural divide presents unique health challenges, with urban areas facing pollution and rural areas dealing with limited healthcare access. High pet ownership (88.76%) and outdoor activities (72.33%) contribute to the spread while sleeping off the ground (78.96%) offers some health benefits.The study emphasizes the need for targeted health interventions to address the specific demographic and environmental challenges influencing CL transmission.